Kajian Tentang Perjanjian FTA antara AFTA dan Cina - Jeong, Young Kyu (Jurnal Ekonomi dan Pembangunan Indonesia, 2004)
This study analyses the prospects, changes and characteristics of economics cooperation between AFTA and China after the period from l980's. Gross trade and direct investments are studies here, as well as tariff such as per categories, field, in order to understand ATTA-China's economic cooperation. According to FTA between AFTA and China, Crude oil, gas and other products took up the greatest portion of AFTA exports until the 2008 (in the short run), since the mid-2003, exports have grown by a large margin owing to the nation's export-oriented economic development strategy. But, in the long run, foreign investment in the world concentrate upon China.